2011
DOI: 10.1007/s13530-011-0093-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chlorpromazine on the onset of puberty and follicular development in immature female rats

Abstract: Effect of chlorpromazine (dopamine receptor antagonist) on pre-pubertal ovarian follicular development and onset of puberty were studied. Fifteen days old female rats were administered chlorpromazine (2.5 mg /kg body weight) daily for 21 days and appropriate controls were maintained. The onset of puberty in immature female rats was delayed following chlorpromazine treatment. There were significant increases in the body weight, ovary weight and diameter of the ovary of controls and treated group over the initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…After 10 mg/kg body weight CPZ administration in rats, Williams et al (4) found a large increase in serum prolactin and a significant drop in testosterone and Luteinizing Hormone (LH). In immature female rats, Ali and Bhagya (5) observed that CPZ causes follicular atresia and delays puberty onset.…”
Section: Introductionmentioning
confidence: 99%
“…After 10 mg/kg body weight CPZ administration in rats, Williams et al (4) found a large increase in serum prolactin and a significant drop in testosterone and Luteinizing Hormone (LH). In immature female rats, Ali and Bhagya (5) observed that CPZ causes follicular atresia and delays puberty onset.…”
Section: Introductionmentioning
confidence: 99%
“…Even though not lethal, it has been described as a radical life changing problem that carries with it significant psychological trauma ( Oyewopo et al, 2018 ). Infertility can be caused by various problems in which synthetic antipsychotic drugs are not exempted ( Ali & Bhagya, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Electronic Medicines Compendium (EMC) reported that there is paucity of information as regards to anti-fertility effects of Chlorpromazine in male animals when compared with female animals, where it has been revealed to decrease fertility parameters ( EMC, 2019 ). Ali & Bhagya (2011) reported that Chlorpromazine results in loss of follicle by atresia and delays the onset of puberty in immature female rats.…”
Section: Introductionmentioning
confidence: 99%